Digestibilidade aparente de farinha de Tenebrio molitor e concentrado proteico de sementes de porongo para jundiás (Rhamdia quelen) - Ebling, Matielle Linhares Pittaluga (2022)
This study aimed at using two unconventional protein sources in the nutrition of silver catfish (Rhamdia quelen), defatted yellow mealworm (Tenebrio molitor) and the protein concentrate of porongo seeds (Lagenaria siceraria), determining the apparent digestibility coefficients (ADCs) of dry matter (DM), crude protein (CP), ether extract (EE), organic matter (OM) and mineral matter (MM) of these ingredients, as well as the performance and digestive indicators of the fish. For the study with yellow mealworm, a method of drying and removing the fat from the larvae was first developed, thus obtaining an ingredient (flour) with higher protein content. To obtain the protein concentrate of porongo seeds, a methodology for protein extraction and concentration was used. Subsequently, experimental diets were prepared according to the requirements of the evaluated species and developmental stage, carrying out a biological assay. Thirty-two silver catfish with an average initial weight of 15.37 ± 2.68g were randomly distributed in six conical-cylindrical incubators (200L) and the experimental design used was completely randomized, with two treatments and three replications. The tested ingredients were included in the proportion of 30% of the test ingredient and 69.98% of the reference diet. Chromium III oxide at a concentration of 0.2% was used as a marker. In the study with defatted yellow mealworm (DYM) high CDAs (>70%) were observed, but when compared to the reference diet, protein and fat excretion in feces was higher with the test diet. In the performance evaluation, significant differences were observed only in the growth parameters (DCM and GMD). In the study with porongo protein concentrate (PPC), statistical differences were observed in the proximate composition of the diets (CP, EE and MM) and feces (EE and CP). There was a statistical difference for the growth parameters (DCM, GMD and CA) and hepatosomatic indicator. In the determination of ADCs, satisfactory values was observed for CP and EE, and acceptable values as verified in the literature. We concluded that both test diets can be considered good options as sources of protein, as they presented good digestibility of the ingredients and did not affect the performance of the silver catfish. It is worth mentioning that further studies should be carried out to improve the appropriate forms and levels of inclusion of these ingredients for each species to be worked, promoting better use of the protein and less impact on the cultivation environment.